融合教室觀察訓練與自我調整學習策略於輔導活動教學實習課程之實踐研究 A Practical Study of Integrating Classroom Observation Training and Self-Regulation Learning Strategies into Guidance Activity Teaching Practicum - 羅家玲 Chia-Ling Luo (Shizi Peiyu Yu Jiaoshi Zhuanye Fazhan Qikan, 2021)
本研究旨在探討研究者改進個人教學之實踐策略結果與反思。基於研究者在教學實習課程的教學經驗與觀察，發現學生常以主觀意見進行教學回饋，以致難有共通的學理進行討論，也缺乏清晰的合作模式，幫助學生有意識地持續練習。故擬嘗試一套融合教學理念、教室觀察訓練與自我調整學習策略的系統性教學模式，透過多元評量與資料分析結 果，以確認此教學策略的可行性，並反思此教學策略作為後續教學研究行動的參考。結果顯示：一、在認知層面上，學生普遍能達到理解和應用有效教學的觀點，以之作為教學分析與回饋的知識基礎。二、學生普遍能理解和應用教室觀察技術於教室觀察中，熟悉教師中心的認知行為訓練模式。三、學生普遍接受自我調整學習策略並獲益，以自選「尋求授課清晰」、「班級經營」、「檢視學習參與」作為自我調整學習的三大主要目標，顯示新手教師在專業發展上主要關注的學習焦點。四、即使至中學實境教學，學生亦能正確應用有效教學學理、應用同儕合作進行教室觀察模式，並進行個人自我調整學習。整體而言，此模式有助於輔導專長職前教師以教學學理與實踐知識的基礎分析教學經驗，並能夠理解、應用、合作和自我調整以改善過去的不足，支持研究者初探此教學策略的可行性。研究者反思教學評量和研究限制等不足，作為後續改善教學實踐行動的參考。 This research aims to explore the results and reflections of the researcher’s practical strategies for improving personal teaching. Based on the researcher’s teaching experience and observations in teaching practice courses, it is found that students often use subjective opinions as teaching feedback, which makes it difficult to discuss based on the same teaching theory, and a clear model of cooperation is also lacking. After the teaching discussion, students need consciously continue to practice. Therefore, the researcher tries on a systematic teaching model that integrates teaching concepts, classroom observation training, and self-regulation learning strategies. Through multiple evaluations and data analysis, the result of this teaching strategy is confirmed. This research also reflects on the teaching strategy as a reference to followup teaching practices. The research results show that: 1. At the level of cognitive learning, generally, students can understand and apply the idea of " effective teaching theory " during classroom observation, which is used as the knowledge basis for teaching analysis and feedback. 2. Generally, students can understand and apply classroom observation techniques in classroom observation, and are familiar with the teacher-centered cognitive behavior training model. 3. Generally, students accept and benefit from selfregulated learning strategies, " Trying to teaching clearly ", " Classroom Management" and "Confirmation of Student Participation " are the three major tasks that most students chose for self-improvement. This shows the learning focuses of novice teachers on their ways of professional development. 4. Even in real teaching field in middle schools, students can correctly apply teaching effectiveness viewpoints and peerto-peer cooperation in classroom observation models to continue personal self-regulation learning. On the whole, this model is helpful for pre-service teachers to analyze teaching experience from the perspective of teaching theory and knowledge, and to understand, apply and cooperate the teaching strategies, to selfregulation learning which finally improves the missing before. The possibility of this teaching strategy used in the research could be supported. The researcher reflects on the teaching evaluation and research limitations of this course, as a reference for follow-up actions to improve teaching practice.